Meningkatkan Kinerja melalui Pengendalian Proses-proses Strategis, Inovasi dan Pengelolaan Sumberdaya - Taufik, Candra; Mulyadi, Hari; Suryana, Suryana; Istardi, Didi (Jurnal Internasional Penelitian Bisnis Terapan, 2026)
This study aims to examine the effect of controlling strategic processes, resource management, and innovation on entrepreneurial performance and firm performance. We analyzed data from 154 entrepreneurs and company managers of the furniture industry sector using PLS-SEM to test several hypotheses. The results show a significant effect of strategic entrepreneurship control on improving resource management, innovation, and entrepreneurial performance. Strategic entrepreneurship control, which integrates strategic entrepreneurship and strategic control, can also indirectly boost firm performance. The practical implications of this research are that to address the problem of declining performance, it is necessary to improve innovation and resource management, as well as control strategic processes through the construct of strategic entrepreneurship control. This research contributes to the field of management science, particularly entrepreneurship, strategic entrepreneurship, and strategic control.